(NbRATI )QÆ POBRATIMI (B:s)E (NROMAN (B/s - (NmEDUNICQ(B, (NmIHAJLO mIHAJLOWI^(B,s; (NmUZIKA(B, (Nw(B. (Nd(B.,s ((NkI)QÇW (B:s)E (NrADQNSXKIJ PISXMENNIK(B,s, 1990)
(NrOMAN(B-(NHRON)QÆKA Z VITTQ KLASIKA UKRAÇNSXKOÇ LÆTERATURI pANASA mIRNOGO TA JOGO BRATA æWANA bÆLIKAs)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NhUDOVNQ L)QÆTERATURAs)E -- (NpROZAs -- (NrOMANIs -- (NuKRA)QÇNAs)E